Upgraded Harmony Search Algorithm for Solving Optimal Reactive Power Dispatch Problem - Lenin, K; Reddy, B Ravindhranath; Suryakalavathi, M (International Journal of Mathematical Research, 2014)
In this paper, a new-fangled Improved harmony search algorithm (IHS) is projected to solve optimal reactive power dispatch problem. Harmony search (HS) is a derivative-free tangible parameter optimization algorithm. It draws encouragement from the musical improvisation process of searching for a perfect state of harmony. The projected opposition-based HS of the present work employs opposition-based learning for harmony memory initialization and also for generation jumping. The perception of opposite number is employed in IHS to improve the convergence rate of the HS algorithm. The proposed IHS has been tested on standard IEEE 57 bus test systems and simulation results show clearly the better performance of the proposed algorithm in reducing the real power loss.